Latin american production on solid waste management in Scopus, 2010 - 2020 - Tito Betancur, Madona (2021)
Solid waste management has become a critical problem in developing countries, therefore, with the aim of analyzing the Latin American scientific production on solid waste management in Scopus, a retrospective descriptive study was conducted considering as the unit of analysis the publications on solid waste management in journals indexed in Scopus, during the period 2010 to 2020. The search included all published and indexed articles, using the fields Article Title, Abstracts, Keywords, having as search term the word "Solid waste management". As result, 494 articles were found, of which 420 are original, 58 are reviews, and the rest are letters, editorials, conference papers, and notes. Brazil stands out as the largest producer of solid waste management knowledge (62.5% of Latin American production), followed by Mexico, Colombia, Chile, and Argentina. On the other hand, 158 international institutions have participated in the Latin American production and only 10 have produced more than 10 articles, with universities in Brazil and Mexico standing out. Among the most productive journals, Waste Management and Waste Management And Research stand out; and the researchers with the most publications are Liséte Lange and Sandro Donnini Mancini. It is concluded that research on solid waste management in Latin America in the period 2010 - 2020 is still deficient compared to other areas of the environmental field. The Latin American countries with the highest production in this area are Brazil, with more than 50%, followed by Mexico, Colombia, Chile, and Argentina.